Laughter Closed up in Horror: The Case of the Hungarian Ballad about a Walled-up Woman - Leszek Hensel (Slavia Meridionalis, 2024)
Laughter Closed up in Horror: The Case of the Hungarian Ballad about a Walled-up Woman The paper is dedicated to a paradox. By approaching the topic of violence, I am actually trying to answer the question of whether and how it is possible to combine it with laughter. I was inspired to adopt this perspective by research on the different types of humorous recycling of one of the most popular works of Hungarian folk literature, the ballad Kőmives Kelemenné [Kelemen Mason’s Wife], which is a story of men’s violence against a woman: the walling-up of the master mason’s wife so that the husband and his team could build a durable castle and receive the agreed payment for their work. The article is based on a rich material base, including both short lexical jokes and longer satires and humorous sketches that have been produced in Hungary since the beginning of the 20th century. In addition to written texts, it refers to humorous drawings published in newspapers and magazines and to versions of the ballad that are present in the internet space. Based on theoretical works by, among others, S. Freud, V. Raskin, R. A. Martin, it seeks an answer to the question of the image of Hungarian society that the analysed materials reflect.   Humor zamknięty w horrorze. Przypadek węgierskiej ballady o zamurowanej kobiecie Artykuł poświęcony jest pewnemu paradoksowi. Podejmując temat przemocy, w istocie próbuje odpowiedzieć na pytanie, czy i jaki sposób jest możliwe jej połączenie ze śmiechem. Do przyjęcia takiej perspektywy skłaniają badania nad różnymi rodzajami humorystycznego recyklingu jednego z najpopularniejszych utworów węgierskiej literatury ludowej – ballady Kőmives Kelemenné [Żona Kelemena Murarza]. Ballada opowiada o zamurowaniu żony mistrza murarskiego, aby mąż i jego współpracownicy mogli zbudować trwały zamek i otrzymać wysoką zapłatę za swoją pracę. Artykuł opiera się na bogatej bazie materiałowej, obejmującej zarówno krótkie żarty leksykalne, jak i dłuższe satyry i humorystyczne skecze, które powstawały na Węgrzech od początku XX wieku do czasów współczesnych. Oprócz tekstów pisanych odwołuje się do humorystycznych rysunków publikowanych w gazetach i czasopismach oraz do wersji ballady obecnych w przestrzeni internetowej. Biorąc za podstawę prace teoretyczne m.in. S. Freuda, V. Raskina, R. A. Martina, autor poszukuje odpowiedzi na pytanie o obraz społeczeństwa węgierskiego, jaki odzwierciedlają analizowane materiały.